(untitled) (Journal of Environmental Science and Natural Resources, 2012)
The purpose of the study was to ascertain the attitude of the peoples towards social forestry and to explore the relationship between the selected characteristics of the respondents and their attitude towards social forestry. Attempt was also made to find out the rank order of attitudinal statements. Local community, local leader and social forestry beneficiaries of Puthia and Charghat Upzila of Rajshahi district constituted the population of the study. A total of 182 respondents were selected as sample. Interview schedule was used for collecting data from the sampled respondents during September, 2011 to December, 2011. The four selected characteristics of the respondents were considered as the independent variables. A 5-point rating scale was used to measure the dependent variable attitude towards social forestry. The findings revealed that near about three-fifths (59.34%) of the respondents had moderately favourable attitude towards social forestry compared to 32.2 percent highly favourable and 8.24 percent slightly favourable attitude towards social forestry. Correlation were used to explore the relationships among the variables. Out of 4 independent variables, age and occupation of all groups of respondents had a negative relationship with their attitude forwards social forestry, whereas education and annual income did not show significant relationship. The comp uted t value indicated that there was no attitudinal significant difference among the three groups. Among the 30 statements by improving local microclimate, social forestry can contribute significantly for the maintenance of ecological balance, important way to create capital, promotion of social forestry can bring improvement in aesthetic view of the area and social forestry will provide harbor to insects, pests and diseases which is detrimental for human health and agricultural production was the 1st, 2nd, 3rd and 4th, respectively. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11585 J. Environ. Sci. & Natural Resources, 5(1): 217 - 222, 2012